Pemupukan N, P, K, Dolomit, dan Pupuk Kandang pada Budidaya Kedelai di Lahan Kering Masam - Hasibuan, Halimatus Syahdia; Sopandie, Didy; ,, Trikoesoemaningtyas; Wirnas, dan Desta (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
The imbalanced supply-demand of soybean is the main reason of soybean import in Indonesia. One of the efforts to increase of soybean production was expanding the planting area to acid soil with a low pH, high content of Aluminum, and low nutrient availability, through giving ameliorant, such as liming organic materials, and mineral fertilization.This study was aimed to obtain the best combination of fertilizer and amelioran for soybean production in acid soil. The study was conducted in experimental station of Tenjo, Bogor from November 2015 to March 2016. The experiment used a randomized complete block design with two factors. The first factor was combinations of fertilizer and amelioran, i.e., P0 (without fertilization); P1 {25 kg urea + 75 kg SP-36 + 50 kg KCl + dolomite ¼ x Aldd (805 kg) ha-1}; P2 {25 kg urea + 75 kg SP-36 + 50 kg KCl + dolomite ¼ x Aldd (805 kg) + 1,250 kg of manure ha-1}; P3 {50 kg urea + 75 kg SP-36 + 50 kg KCl + dolomite ¼ x Aldd (805 kg) + 2,500 kg of manure ha-1}; P4 {75 kg urea + 150 kg SP-36 + 100 kg KCl + dolomite ¼ x Aldd (805 kg) + 2,500 kg of manure ha-1}; P5 {75 kg urea + 150 kg SP-36 + 100 kg KCl + dolomite ½ x Aldd (1,610 kg) ha-1}; P6 {75 kg urea + 150 kg SP-36 + 100 kg KCl + dolomites 1 x Aldd (3,220 kg) ha-1}. The second factor was soybean varieties of Tanggamus and Anjasmoro. The results showed that application of 75 kg urea + 150 kg SP-36 + 100 kg KCl + dolomite ½ x Aldd (1,610 kg) produced the highest productivity (2.91 ton ha-1), but it was not different from reducing the dose of dolomite into ¼ x Aldd (805 kg) with the addition of 2,500  kg of manure.